Influence of humidity on radon and thoron exhalation rates from building materials. (January 2015) - Janik, M.; Omori, Y.; Yonehara, H.
Abstract: The contributions of radon and thoron from building materials to total radon (thoron) entry rates in dwellings range from almost zero to several percent. It is necessary to measure radon and thoron exhalation rates, among other things, to assess the radiological hazard to human health in a living environment. Brick and granite specimens were used to study the changes of these rates as a function of the relative and absolute humidities. Measurement results showed that radon and thoron exhalation rates change to humidity with the same trends as well as effective dose could be changed by the factor of 2 due to this. Abstract : Highlights: Humidity has significant effect on radon and thoron exhalation rates. The exhalation rate tendency was the same for samples with different porosity and density. Humidity effect should be considered for calculation of the equivalent dose from radon and thoron.